2021
DOI: 10.31436/hs.v1i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of L-cysteine Sources using FTIR and Raman Spectroscopy

Abstract: L-cysteine is a food additive that is used in bakery ingredient. It is used as stabilizer to soften the texture of bakery dough. However, the primary sources of L-cysteine could be controversial as it might derive from animal and human parts. This study aimed to differentiate the L-cysteine sources by using Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) and Raman spectroscopy. Raw materials of pig bristles, human hair, cow horn, duck feather and chicken feather were analysed. The result foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…FTIR spectra were applied to study the functional groups of free cysteine, HA, and Cys‐ conj ‐HA molecules (as shown in Figure 1C). In the FTIR spectrum of free cysteine, the diffraction peak found at 1600 cm −1 was due to the vibration of carbanyl group in COOH 38 . As to HA molecules, the diffraction peak observed at 1556 cm −1 could be attributed to the vibration of NH moieties.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…FTIR spectra were applied to study the functional groups of free cysteine, HA, and Cys‐ conj ‐HA molecules (as shown in Figure 1C). In the FTIR spectrum of free cysteine, the diffraction peak found at 1600 cm −1 was due to the vibration of carbanyl group in COOH 38 . As to HA molecules, the diffraction peak observed at 1556 cm −1 could be attributed to the vibration of NH moieties.…”
Section: Resultsmentioning
confidence: 95%
“…In the FTIR spectrum of free cysteine, the diffraction peak found at 1600 cm À1 was due to the vibration of carbanyl group in COOH. 38 As to HA molecules, the diffraction peak observed at 1556 cm À1 The second one was start at 186.5 C and terminated at 497.3 C with the mass loss of 55.6%, which might be caused by the pyrolysis of HA molecules. 39 By contrast, cysteine molecules showed the lowest thermal stability.…”
Section: Discussionmentioning
confidence: 95%
“…Activated carbon (6 g) was added to remove color, and the mixture was left to stand for 24 hours. After decantation to separate the activated carbon, the sample was filtered using a Buchner funnel, and any remaining solid residue was rinsed twice with distilled water 17 . The formed solid was dissolved in 100 mL of 40% NaOH with stirring.…”
Section: Amino Acid Isolationmentioning
confidence: 99%